Forward and Inverse Robotics Kinematics JavaScript-HTML5 Simulator - Spyridon Mitropoulos; Odysseas Tsakiridis; Ioannis Christakis (Proceedings)
The development of technology nowadays, and specifically in the field of robotics, is an increasingly developed field of research and development by the scientific community to optimize its productivity [...]